Dimesitylboryl-functionalized tetraphenylethene derivatives: efficient solid-state luminescent materials with enhanced electron-transporting ability for nondoped OLEDs. Issue 23 (20th May 2016) - Chen, Long; Lin, Gengwei; Peng, Huiren; Nie, Han; Zhuang, Zeyan; Shen, Pingchuan; Ding, Siyang; Huang, Dijie; Hu, Rongrong; Chen, Shuming; Huang, Fei; Qin, Anjun; et al.
Abstract : Efficient n-type emitters are prepared from dimesitylboryl-functionalized tetraphenylethene derivatives. Abstract : Organic electroluminescent materials that can simultaneously serve as light-emitting and electron-transporting layers in one organic light-emitting diode (OLED) are very useful for simplifying device configuration, but there are not many. In this work, three tailored luminescent materials (TPE-DB, TPE-BPDB and TPE-TPDB) adopting tetraphenylethene (TPE) and dimesitylboryl groups as the π-conjugated backbone and the electron-deficient functional group, respectively, are synthesized and fully characterized. Their thermal, photophysical, electronic, electrochemical, and electroluminescent properties are investigated systematically. The results reveal that these new dimesitylboryl-functionalized TPE derivatives feature aggregation-induced emission (AIE) characteristics with high fluorescence quantum yields of 81–86% in solid films. They possess high glass-transition temperatures of 134–168 °C and very low LUMO energy levels down to −2.9 eV. The OLED device [ITO/HATCN (20 nm)/NPB (40 nm)/TPE-DB (60 nm)/LiF (1 nm)/Al (100 nm)] that is fabricated by adopting TPE-DB as both the light emitter and electron transporter exhibits excellent electroluminescent performance, with high efficiencies of up to 13.5 cd A −1 and 4.6%, which are advanced noticeably relative to those attained from the device with an additional electron-transporting layer (TPBi). The results demonstrate that these new TPE derivatives are promising n-type solid-state luminescent materials with practical utility in nondoped OLEDs.